LITERATURE REVIEW: DETERMINASI KEPATUHAN WAJIB PAJAK UMKM MELALUI DJP ONLINE - Supriyadi, Agung; Chandra, Aditya Kurniawan; Lestari, Angelica Ivone Putri; Yanti, Febry Cristi; Gitama, Gytha Nurhana Dhea Praadha (Jurnal EBI, 2023)
Tax is one of the main sources of state revenue for Indonesia. However, the awareness level of taxpayers is still low and is a big problem for the state. This is evident from the fact that the number of MSMEs in Indonesia is greater than the number of taxpayers registered with the DGT, which is 8.71 million business units in 2022. Therefore, the DGT has developed DGT Online, which is a digital platform that allows MSMEs to manage and comply with their tax obligations electronically. This research was conducted to analyze how much influence DGT Online has, tax sanctions, taxpayer awareness, and service quality on the level of taxpayer compliance in fulfilling their obligations. The method used in this research is qualitative research with a literature study approach. The results of this study indicate that the application of technology in tax administration, such as e-Registration, e-Filing, and e-Billing, has a positive impact on the level of taxpayer compliance. This technology not only simplifies the process of reporting and paying taxes, but also improves the efficiency and accuracy of reporting, reduces the potential for errors, and provides significant benefits for taxpayers in fulfilling their tax obligations.Keywords: DJP Online, Taxpayer Compliance, Technology